Enhancing Alumni Data Management through a Website-Based Tracer Study Application: A Case Study of Vocational High School - Wahjusaputri, Sintha; Bunyamin, Bunyamin; Widyaningtyas, Arista; Salamah, Siti Afiyatus; Anjaryani, Siwi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to evaluate the effectiveness of website-based tracer studies in collecting data on educational institutions and their alumni. The research methodology employed is A quasi- experimental design, specifically a Pretest-Posttest Control Group Design, was employed to establish cause-and-effect relationship.  The result indicates that 20% of teachers met the minimum completeness criteria using the web-based application, while 80% did not. The experimental group showed improvement form pre-test to post test, meeting the minimal criteria for completeness. Challenges included difficulties in contacting alumni, which impacted data collection. The study concludes that while the web-based tracer study application is effective, challenges in alumni engagement need to be addressed for better data collection.